Treatment results of patients with multiple and extensive drug resistance registered in 2012 in the Russian Federation and in the world - S. A. Sterlikov; V. V. Testov; I. A. Vasilieva (Туберкулез и болезни лёгких, 2016)
The chemotherapy results have been analyzed in tuberculosis patients suffering from multiple drug resistance registered for treatment in the Russian Federation in 2011-2012 compared with the treatment outcomes of MDR patients registered for treatment in the world, BRICS and countries of the former Soviet Union in 2011. Treatment outcomes of XDR TB patients have been analyzed for the first time. Chemotherapy efficiency in MDR TB patients in the Russian Federation in the cohort of 2011 made 37.1%, and in the cohort of 2012 made 39.1%, which significantly lower than in the world in general (47.5%), in BRICS and countries of the former Soviet Union; this low treatment efficiency is mostly due to treatment failures (18.3%) and those died (19.1%). The treatment efficiency of XDR TB patients registered for treatment in the Russian Federation in 2012 made 26.2% versus 22.0% in the cohort of 2011. Considering the significant financial costs spent on the treatment, the chemotherapy efficiency of M/XDR TB patients in the Russian Federation is too low to improve the epidemic situation and some additional measures are to be taken for its improvement.